2013
DOI: 10.1002/app.39938
|View full text |Cite
|
Sign up to set email alerts
|

Solid state grafting copolymerization of acrylamide onto poly(vinyl alcohol) initiated by redox system

Abstract: A solid state grafting copolymerization of acrylamide (AM) onto poly(vinyl alcohol) (PVA) was conducted with ammonium persulfate and sodium bisulfite redox system as initiators. Before the reaction the PVA powder and required amount of AM were mixed evenly, and sprayed with water to swell the PVA powder and to dissolve AM. Then the swollen PVA powder was sprayed with the redox solution, and the reaction temperature was controlled at a temperature between 30 C and 80 C for 120 min. The grafting percentage and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Similar mechanical behaviors such as increased elastic modulus and reduced tensile strength were also observed in the literature after the solid‐state graft copolymerization of acrylamide to the PVA, and these behaviors were related to the hydrogen bonding between the grafted chains and polymer backbone. According to this, after changing the nature of the HPET surface with PVA grafting, the possibility of hydrogen bonding would increase, and thus, the elastic modulus of the PVA‐ g ‐HPET also increase.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Similar mechanical behaviors such as increased elastic modulus and reduced tensile strength were also observed in the literature after the solid‐state graft copolymerization of acrylamide to the PVA, and these behaviors were related to the hydrogen bonding between the grafted chains and polymer backbone. According to this, after changing the nature of the HPET surface with PVA grafting, the possibility of hydrogen bonding would increase, and thus, the elastic modulus of the PVA‐ g ‐HPET also increase.…”
Section: Resultssupporting
confidence: 82%
“…The increase in the elastic modulus of the HPET compared with the UPET fabrics up to 6 mm elongation might be attributed to the hydrogen bonds occurred in the chain ends (between the carboxyl and/or hydroxyl sides) of the PET backbone after the alkaline hydrolysis . Because it has been reported in the literature that the elastic modulus of a polymer was related to the interaction of the polymer chains, the tensile strength was correlated with the molecular weight of a polymer . During the application of the tensile load in this region, the hydrogen bonds between the polymer chains in the HPET fabrics might be broken.…”
Section: Resultsmentioning
confidence: 97%
“…The spectrum of Gel‐0 (PAM/PVA) exhibited peak shifting at 3294 cm −1 due to the overlapping of amide groups of PAM and −OH groups of PVA, which indicated the formation of strong hydrogen bonding between those groups 30 . The new characteristic peak at 1657 cm −1 was attributed to the C=O stretching vibration of primary amide, which was evidence of grafted PAM on the PVA backbone 31 . In the spectra of PAM/PVA/Gel, the peaks corresponding to PAM/PVA appeared with some shifts.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the water solubility of PVA of high degree of alcoholysis, a great number of methods based on copolymerization or post-polymerization modication (esterication occurring on the hydroxyl group or Ce(IV) initiated radical polymerization occurring on the methane/ hydroxyl groups in PVA chain) to introduce hydrophilic groups for improving solute-solvent interactions and/or enhance steric hindrances for suppressing crystallinity of PVA chain have been reported. [12][13][14] Recent studies 15 found that a noticeable increase of solubility of PVA can be achieved by esterifying PVA with D,L-lactic acid possibly due to the synergism of the increase in steric hindrances and the decrease in alcoholysis degree. However, investigations of the similar PLA modied PVA by Ding et al 16 obtained non-water-soluble polymers in all cases.…”
Section: Introductionmentioning
confidence: 99%